1994
DOI: 10.1051/agro:19940208
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield, carbon isotope discrimination and mineral content in mature kernels of barley under irrigated and rainfed conditions

Abstract: under rainfed conditions. Carbon isotope discrimination and ash content together account for almost 60% of the variation in yield, in both conditions. There was no significant relationship (r=-0.15) between carbon isotope discrimination and ash content in well-irrigated plants, whereas in rainfed plants, this relationship, although significant (r=-0.54, P< 0.05), was weakly negative. The concentration of several mineral elements was measured in the same kernels. The mineral that correlated best with ash conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
8
11
1
Order By: Relevance
“…1995). The negative correlation registered under the RSMS treatment between m a G m and yield has previously been reported in barley (Febrero et al. 1994, Voltas et al.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…1995). The negative correlation registered under the RSMS treatment between m a G m and yield has previously been reported in barley (Febrero et al. 1994, Voltas et al.…”
Section: Discussionsupporting
confidence: 70%
“…Correlation was found between D, leaf m a and grain yield in different C 3 species by Masle et al (1992), Mayland et al (1993), Merah et al (1999Merah et al ( , 2001a and Tsialtas et al (2002). Febrero et al (1994), Voltas et al (1998) and Merah et al (1999Merah et al ( , 2001a) also reported a negative correlation between m a in grain and grain yield of winter cereals grown under Mediterranean conditions. These correla-tions were, however, weaker than those between grain D and grain yield.…”
Section: Introductionmentioning
confidence: 90%
“…The other three parameters i.e., internal CO 2 concentration, stomatal conductance and transpiration rate did not show any significant correlation with the leaf yield except that of water use efficiency, which had a very strong positive correlation with the leaf yield. Similar type of strong correlation between WUE and yield was observed in barley (Febrero et al, 1994). Likewise, photosynthetic rate was positively correlated with the shoot dry weight of cotton (Brugnoli and Lauteri, 1990).…”
Section: Resultssupporting
confidence: 76%
“…To reduce the high cost of Δ analysis, many previous studies have suggested that foliar ash content and K concentration could be used as cheap, putative surrogates of Δ (Febrero et al 1994, Merah et al 2001a, Misra et al 2006, Tsialtas et al 2002. In this study, the significantly positive relationships between Δ and ash content in both P. euphratica and T. ramosissima were revealed.…”
Section: Discussionmentioning
confidence: 55%
“…3). Grain in bread wheat and barley (Masle et al 1992, Febrero et al 1994 and in C. korshinskii (Zhao et al 2007) as well as seed cotton (Tsialtas et al 2008) were also found in the same negative correlation. Those show that a passive transport of K nutrients through the transpiration stream is not the only factor that determines mineral content in P. euphratica, and that K plays an important role in regulating stomatal functions as well as showing that K is an easily lapsed nutrient element.…”
Section: Discussionmentioning
confidence: 61%